Materials science and technology : a comprehensive treatment. Vollume 12, Structure and properties of polymers / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : Edwin L. Thomas - Thomas, Edwin L.
Vol. 12 Structure and properties of polymers in 1993